Sir Cumference And The Roundabout Battle : A Math Adventure - Cindy Neuschwander (Charlesbridge Publishing,U.S., 2015)
When Steward Edmund Rounds and Sir Cumference notice that there are strangers camped nearby, Rounds II decides to investigate despite being involved with the task of learning how to make accurate counts of the castle's stores of food, supplies, and weaponry. When he reports back that an enemy is lying in wait, everyone moves quickly to defend the castle. But wait! Will Rounds II be able to figure out how many bows and arrows they have to create an appropriate battle plan? Using rounding techniques to figure out the totals more quickly, Rounds II is just in time to help stave off a potentially disastrous attack.
Keywords: Math Stories